2015
DOI: 10.1586/14737175.2015.1091727
|View full text |Cite
|
Sign up to set email alerts
|

Treating non-motor symptoms of Parkinson’s disease with transplantation of stem cells

Abstract: Summary Parkinson’s disease (PD) treatment-based research has focused on developing therapies for the management of motor symptoms. Non-motor symptoms do not respond to treatments targeting motor deficits, thus necessitating an urgent need to develop new modalities that cater to both motor and non-motor deficits. Stem cell transplantation is potentially therapeutic for PD, but the disease non-motor symptoms have been primarily neglected in such cell therapy regimens. Many types of stem cells are currently avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…Due to the selective degeneration of neurons in PD, cell-based therapies including neuronal transplantation were viewed as compelling therapeutic approaches. The proposed mechanisms of cell transplantation that allow for the mitigation of neurodegeneration and symptoms include neurite outgrowth of grafts, graft innervation, and formation of synaptic connections with the host tissue 25 , the expression of tyrosine hydroxylase, the release of dopamine, and the release of neurotrophic and neuroprotective bioactive molecules from the transplanted cells 26,27 .…”
Section: Evolution Of Cell Therapy For Treatment Of Pdmentioning
confidence: 99%
“…Due to the selective degeneration of neurons in PD, cell-based therapies including neuronal transplantation were viewed as compelling therapeutic approaches. The proposed mechanisms of cell transplantation that allow for the mitigation of neurodegeneration and symptoms include neurite outgrowth of grafts, graft innervation, and formation of synaptic connections with the host tissue 25 , the expression of tyrosine hydroxylase, the release of dopamine, and the release of neurotrophic and neuroprotective bioactive molecules from the transplanted cells 26,27 .…”
Section: Evolution Of Cell Therapy For Treatment Of Pdmentioning
confidence: 99%
“…Therefore, PD is clinically recognized by a core of motor symptoms, including bradykinesia, rigidity, tremor, and postural instability, which are used in the establishment of its diagnosis [6]. However, non-motor symptoms, such as depression, sleep disorders, dementia, and peripheral impairments, have also been linked with functional disabilities, preceding the appearance of the motor symptomatology [7]. Thus, the development of management strategies is crucial, in which the diagnosis and the evaluation of the condition of the patient should be accurate, being followed by the development and application of personalized strategies, aiming to ameliorate the patient’s quality of life [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that high cadence cycling may increase sensory feedback; activating basal ganglia circuits to enhance central motor processing may explain these favorable motor function results. However, it is possible that this approach is favorable for targeting motor symptoms, not non-motor symptoms [46,47,48]. Non-motor symptoms of PD are regulated by multiple non-dopaminergic neurotransmitters; thus, common levodopa and other pharmacological dopamine therapies may not address associated neurotransmitter dysfunction [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that this approach is favorable for targeting motor symptoms, not non-motor symptoms [46,47,48]. Non-motor symptoms of PD are regulated by multiple non-dopaminergic neurotransmitters; thus, common levodopa and other pharmacological dopamine therapies may not address associated neurotransmitter dysfunction [48,49]. Interestingly, reports suggest that non-motor symptoms, such as depression, may have an “inconsistent relationship [with the] severity of motor symptoms” [50,51].…”
Section: Discussionmentioning
confidence: 99%